Study of aluminium doped zinc oxide nanofilms deposited by rf magnetron sputtering. (August 2014) - Yu, S.; Wei, Z.; Dong, X. X.; Wang, Y.
Abstract : The transparent conductive films can be widely applied into transparent electrode, liquid crystal displays, solar cells and various optoelectronic devices because of its excellent conductivity and transparency. In this paper, aluminium doped zinc oxide (ZAO) nanofilms are prepared by radio frequency magnetron sputtering. By analysing the results of X-ray diffraction (XRD) and scanning electron microscopy (SEM), it is found that the films prepared have preferred orientation. The properties of ZAO films prepared by magnetron sputtering are controlled by the dopant concentration. X-ray diffraction and SEM show that the increase in dopant concentration may lower the quality of crystallisation. Aluminium doped zinc oxide films can adjust band gaps over quite a large range. Instead of forming a new compound (e.g. Al2 O3 ), Al doping just enables A1 3+ to replace Zn 2+, causing distortion in the crystal lattice. Comparing the optical transmittance in visible light of ZAO samples annealed under 400°C with ones without annealing, no big difference is observed. The transmittance of both samples stay over 90%. The annealing process can improve the electrical properties of thin films, while the oxygen/argon ratio has less impact on the film transmittance. The results indicate that the conductivity of ZAO films have been improved significantly than that of pure zinc oxide films, thus improving the conductivity.